Cross-country analysis of strategies for achieving progress towards global goals for women’s and children’s health - Ahmed, Syed Masud; Rawal, Lal B.; Chowdhury, Sadia A.; Murray, John; Arscott-Mills, Sharon; Jack, Susan; Hinton, Rachael; Alam, Prima M.; Kuruvilla, Shyama (© Bulletin of the World Health Organization 2016, 2018)
This article was published in the Bulletin of the World Health Organization, Population and Nutrition [© 2016 by Bulletin of the World Health Organization ] and the definite version is available at : http://dx.doi.org/10.2471/BLT.15.168450. The Journal's website is at: http://www.who.int/bulletin/volumes/94/5/15-168450/en/